2000 Proceedings. 50th Electronic Components and Technology Conference (Cat. No.00CH37070)
DOI: 10.1109/ectc.2000.853388
|View full text |Cite
|
Sign up to set email alerts
|

Vibration fatigue of μBGA solder joint

Abstract: This paper studies the vibration fatigue failure of pBGA solder-joints reflowed with different temperature profiles, and ageing at 120°C for 1,4,9, 16,25, 36 days. The effect of the thickness of the Ni3Sn4 and Cu-Sn intermetallic compound (IMC) on the fatigue lifetime is also reported. During the vibration fatigue test, in order to identify the failure of pBGA solder joint, electrical interruption was monitored continuously through the daisy-chain network. Our results show that the fatigue lifetime of the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…5) Thick intermetallic compound layer poses potential reliability issues due to an 8.5% and 5% volume shrinkage during the transformation from solid phase to the Cu 3 Sn and Cu 6 Sn 5 intermetallics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5) Thick intermetallic compound layer poses potential reliability issues due to an 8.5% and 5% volume shrinkage during the transformation from solid phase to the Cu 3 Sn and Cu 6 Sn 5 intermetallics.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] The BGA package has been successfully applied in many electronic products. [4][5][6] There are an increasing number of higher density BGA substrates that use immersion Au/electroless Ni for the surface finish. The principal advantage of electroless plating is the ability to meet the requirements of increasing in the terminal density.…”
Section: Introductionmentioning
confidence: 99%
“…1, the 183 C melting temperature of the eutectic solder is defined as the reference temperature line-the liquidus. In our previous work [10], it was found that the integral of the measured temperature above the liquidus line with respect to time, defined as "heating factor," can characterize the reflow profile in the melting section.…”
Section: Methodsmentioning
confidence: 99%
“…The IMC layer thickness increases almost linearly with the heating factor (Tao, 2006). Hence, heating factors of all the solder joints in a PCBA should be controlled within a certain range (such as 200-700 s 8C) to obtain high reliability and soldering quality (Tu and Chan, 2000b; Figure 2). Since the IMC formation mechanism for Sn-Ag-Cu solder paste is fundamentally the same as that for Sn-Pb solder paste (Harris, 1998), the heating factor based optimization of a reflow profile can also be applied to Sn-Ag-Cu solder paste.…”
Section: Introductionmentioning
confidence: 99%